Olaj, olaj, olaj! (5-8 rész) . Oil, Oil, Oil! – part 5-8 - Kóthy, Judit (Kóthy, Judit, 2007)
Chapters from the history of the Hungarian crude oil and natural gas industry. Who are the people that make history? Is it the politicians, the heads of state, the generals, the businessmen? It can seem as if history revolved solely around them. Not even the historian of the 20th century paid much attention to the connections between engineering, economic processes and political events. The heroes of this series are geologists, oil miners, engineers and laborers. While engaged in their daily work they hardly considered the fact that they might be not only getting on with their lives but also making history. The second half of the series tells the story from 1957 to the mid-1980s.